El vacío urbano como oportunidad para la revitalización de la zona centro de Palmira Valle. (2020)
In this research work, urban gaps are addressed both from a theoretical perspective - given the conceptual divergence presented by different authors - and from their actions in reality, how they are perceived, what impact they generate in society, what generates and how these phenomena can be solved from the urban-architectural perspective, without neglecting the sociocultural. Through exploratory research, it is explained through the historical development of Palmira, the multiple ways in which those urban voids are manifested, their characterization and their treatment that is in charge of the local state institutions that capture it in the Development Plan. Municipal and the Land Use Plan. Finally, alternatives are generated to solve this social phenomenon, recover both public space and the social fabric and thus be able to revitalize the central area of the municipality of Palmira.